ENSINO SUPERIOR: INSTRUMENTO DE MOBILIDADE ECONÔMICA? LIÇÕES DA EXPERIÊNCIA DE ALTERNATIVAS DE ACESSO DA UNBENSINO SUPERIOR: INSTRUMENTO DE MOBILIDADE ECONÔMICA? LIÇÕES DA EXPERIÊNCIA DE ALTERNATIVAS DE ACESSO DA UNB - Cláudia Rosana de Araújo Costa (Universidade Federal de Santa Catarina, 2015)
This work was devoted to analyzing the characteristics of origin of the candidates to higher education impact your approval and opting for a particular course, reflecting on his future earnings and consequently on occupational mobility and distributive of the economic system. Therefore, it was done an analysis of the socioeconomic profile of students approved at the University of Brasilia between 2009 and 2013 in two forms of entry: The Vestibular (System Universal and Policies Quotas for Blacks and Students of Public Schools) and the Serial Evaluation Program. The results contradict the Human Capital Theory and reinforce Theories Structuralists, in that show that there are barriers to economic mobility resulting from variables related to the origin of each individual. It was concluded that the Brazilian Higher Education has been an instrument of confirmation of the origins of the students and, in this context, state intervention, especially, through legislation, has an important role in the correction of distortions in the supply of this good, changing levels of regressivity in the allocation of public resources and improving income distribution.